Типи мікроструктури щитоподібної залози при затримці внутрішньоутробного розвитку = Types of microstructure thyroid intrauterine growth retardation - Sokolova, S. S.; Yakovtsova, I. I.; Sergiyenko, L. Yu. (Journal of Education, Health and Sport, 2016)
Sokolova S. S., Yakovtsova I. I., Sergiyenko L. Yu. Типи мікроструктури щитоподібної залози при затримці внутрішньоутробного розвитку = Types of microstructure thyroid intrauterine growth retardation. Journal of Education, Health and Sport. 2016;6(6):146-154. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55157 http://ojs.ukw.edu.pl/index.php/johs/article/view/3564 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. ТИПИ МІКРОСТРУКТУРИ ЩИТОПОДІБНОЇ ЗАЛОЗИ ПРИ ЗАТРИМЦІ ВНУТРІШНЬОУТРОБНОГО РОЗВИТКУ С. С. Соколова 1,2, І. І. Яковцова 2, Л. Ю. Сергієнко 1 1 ДУ «Інститут проблем ендокринної патології ім. В. Я. Данилевського НАМН України», Харків; 2 Харківська академія післядипломної освіти, Харків Резюме Метою дослідження було визначення морфологічної будови ЩЗ мертвонароджених плодів та новонароджених дітей з низькою вагою, що є провідним показником ЗВУР, та визначення частоти пов’язаності цього синдрому та загибелі плодів/дітей з тютюнопалінням матері під час вагітності. При гістологічному дослідженні ЩЗ плодів/дітей нами знайдено, що типи будови тироїдної паренхими співпадають з терміном загибелі плодів, гестаційним віком при народженні та тривалістю післянатального життя. Десквамативний тип мікроструктури ЩЗ плодів притаманний загиблим внутрішньоутробно на 23-27-ому тижні гестації. Змішаний тип спостерігається у народившихся живими, як доношеними, так і недоношеними, але прожили від 7 діб до 3-х тижнів. Фолікулярно-колоїдним типом характеризуються ЩЗ доношених дітей, тривалість післянатального життя яких була найбільшою. Ключові слова: мікроструктура щітоподібної залози, затримка внутрішньо утробного розвитку, типи щитоподібної залози. TYPES OF MICROSTRUCTURE THYROID INTRAUTERINE GROWTH RETARDATION S. S. Sokolova 1,2, I. I. Yakovtsova 2, L. Yu. Sergiyenko 1 1 SI “V. Danilevsky Institute for Endocrine Pathology Problems of the NAMS of Ukraine”, Kharkiv; 2 Kharkiv Medical Postgraduate Academy Clinical and morphological studies have shown that abuse in a state of functional system "mother-placenta-fetus" with the development of feto-placental insufficiency or intrauterine growth retardation (IUGR) of the fetus leading to underdevelopment of the thyroid gland in the fetal period and the occurrence of hypothyroidism in pislyanatalnomu life. But remains unclear what type of structure inherent thyroid fetuses / newborn who died at some stage anti / postnatal life and which had marked by the presence of IUGR. The objective was to study the morphological structure of thyroid stillborn fetuses and newborns with low birth weight, which is the main indicator of IUGR, and determining the frequency of the correlation of this syndrome and death fetuses / bebies with the mother smoking during pregnancy. Histological examination of the thyroid fetuses / bebies we have found that the types of thyroid parenchyma structure coincide with the term of the death of fetuses with a gestational age at birth and duration of postnatal life. Desquamative type of microstructure thyroid fetuses typical for the dead in utero at 23-27-th week. gestation. Mixed observed in live births, both full-term and preterm, but been resident from 7 days to 3 weeks. Follicular colloid-type characterized by thyroid term infants, the duration of which was the greatest life. Keywords: microstructure of the thyroid gland, intrauterine growth retardation, the types of thyroid gland. ТИПЫ МИКРОСТРУКТУРЫ ЩИТОВИДНОЙ ЖЕЛЕЗЫ ПРИ ЗАДЕРЖКЕ ВНУТРИУТРОБНОГО РАЗВИТИЯ Соколова С. С.1,2, Яковцова И. И.2, Сергиенко Л. Ю.1 1ГУ «Институт проблем эндокринной патологии им. В. Я. Данилевского НАМНУкраины», Харьков; 2Харьковская академия последипломного образования, Харьков Целью исследования было изучение морфологической структуры ЩЖ мертворожденных плодов и новорожденных детей с низкой массой, которая является главным показателем ЗВУР, и определение частоты корреляции этого синдрома и гибели полодов/детей с табакокурением матери во время беременности. При гистологическом исследовании ЩЖ плодов/детей нами выяснено, что типы строения тиреоидной паренхимы совпадают со сроком гибели плодов, с гестационным возрастом при рождении и длительностью постнатальной жизни. Десквамативный тип микроструктуры ЩЖ плодов характерен для погибших внутриутробно на 23-27-й нед. гестации. Смешанный тип наблюдается у рожденных живыми, как доношенными, так и недоношенными, но прожившими от 7 суток до 3-х нед. Фолликулярно-коллоидным типом характеризуются ЩЖ доношенных детей, продолжительность жизни которых была наибольшей. Ключевые слова: микроструктура щитовидной железы, задержка внутриутробного развития, типы щитовидной железы.